Microwave propagation and remote sensing atmospheric influences with models and applications - Karmakar, Pranab Kumar (CRC Press, 2012)
This reference offers a brief, elementary account of microwave propagation through the atmosphere and discusses radiometric applications in the microwave band used to characterize and model atmospheric constituents, which is also known as remote sensing